Capital income taxation and household saving - Anne Kerttula (Bank of Finland, 1989)
This paper studies capital income taxation and household saving from three different points of view. Firstly, we work through the effects of capital income taxation in a life cycle model. There are income and substitution effects to consider, and the relative magnitude of these will determine the final outcome. Secondly, we study some long-run issues related to capital income taxation. It has quite a. few long-run effects that need to be considered if we are to use it as a policy instrument. Finally, we have a look at how the actual tax system treats the return to savings. In practice, capital income tends to be lightly taxed because of various provisions.
URN:NBN:fi:bof-201908051347
Keywords: 330